An Introduction to OxMetrics 6. - Doornik, J (Timberlake Consultants Ltd, 2009)
OxMetrics™ is an interactive graphics-oriented program, which acts as “front-end” to a series of integrated software modules: PcGive, Ox, STAMP, G@RCH and X12Arima. OxMetrics provides a complete separation of the front-end (for data manipulation and visualisation) and the econometric and statistical modules, while maintaining a reliable communication channel, and giving a closely integrated appearance from the user perspective. OxMetrics displays reports and graphics, which can be manipulated on screen, offers a calculator and algebraic language for transforming data, and enables the user to open multiple databases. A batch language allows for automation of many of these tasks. OxMetrics reduces the learning curve for econometric and statistical packages by providing a common front-end which is easy to use. Users with the necessary programming skills can write programs in suitable languages (including Ox) which can communicate with OxMetrics.